Mechanical behaviour of composites and laminates - Green, W. A.; Micunovic, M.; European Mechanics Colloquium 214 'Mechanics Behaviour of Composites and Laminates ( 1986: Yugoslavia ) (London: Elsevier Applied Science, 1987)
09